2022
DOI: 10.1088/1758-5090/ac8dc9
|View full text |Cite
|
Sign up to set email alerts
|

Sutureless transplantation of in vivo priming human mesenchymal stem cell sheet promotes the therapeutic potential for cardiac repair

Abstract: Heart, contrary to its small size, vigorously pumps oxygen and nutrients to our entire body indeterminably; and therefore, its dysfunction could be devastating. Until now, in applying cardiac patch for the treatment for myocardial infarction (MI), there are several major obstacles, including poor integration and low engraftment rate due to the highly-curved surface of the heart and its dynamic nature. Here, we demonstrate a novel way for a comprehensive cardiac repair achieved by the sutureless transplantation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Elastin plays an important role in the stimulation of cell signaling cascades associated with proliferation and angiogenesis [ 274 ]. Elastin-like recombinamers (ELRs) are bio-engineered polypeptides with pentapeptide (VPGXG) repeat, where X can be any amino acid excluding proline [ 275 ].…”
Section: Induction Of Angiogenesis Using Scaffolds For Muscle Regener...mentioning
confidence: 99%
“…Elastin plays an important role in the stimulation of cell signaling cascades associated with proliferation and angiogenesis [ 274 ]. Elastin-like recombinamers (ELRs) are bio-engineered polypeptides with pentapeptide (VPGXG) repeat, where X can be any amino acid excluding proline [ 275 ].…”
Section: Induction Of Angiogenesis Using Scaffolds For Muscle Regener...mentioning
confidence: 99%
“…In addition, transplantation of BM-MSC sheets in a model of rat MI enhanced initial retention and amplified subsequent paracrine effects to recover damaged heart, compared with intramyocardial injection [74]. In one study, researchers showed that the sutureless transplantation of aligned a BMSC/HUVEC stacked sheet enhancing the in vivo priming, reduced the fibrosis, and increased the angiogenesis in the injured heart [75]. Miyahara and colleagues evaluated the therapeutic effects of autologous transplantation of single-layer adipose tissue-derived MSCs sheets in a MI rat model.…”
Section: Mscs-based Cell Sheetsmentioning
confidence: 99%
“…The left ventricular internal dimension at end-diastole (LVIDd) and left ventricular internal dimension at endsystole (LVIDs) were measured using the two-dimensional (2D) targeted M-mode to calculate the left ventricular ejection fraction (LVEF) and left ventricular fractional shortening (LVFS). LVEF and LVFS were calculated using the following equations [7,9,31,35]:…”
Section: Echocardiographymentioning
confidence: 99%